(untitled) (American Journal of Islam and Society, 2019)
The Speaking Qur’an is Timur R. Yuskaev’s first book and emerges from his dissertation work at UNC. Yuskaev’s approach to Islamic studies focuses on lived religion in the American context, at the intersection of hermeneutics of sacred text, memory, and linguistic studies.